Direct Measurement of Interparticle Forces of Titan Aerosol Analogs ("Tholin") Using Atomic Force Microscopy. Issue 12 (8th December 2017) - Yu, Xinting; Hörst, Sarah M.; He, Chao; McGuiggan, Patricia; Bridges, Nathan T.
Abstract: To understand the origin of the dunes on Titan, it is important to investigate the material properties of Titan's organic sand particles on Titan. The organic sand may behave distinctively compared to the quartz/basaltic sand on terrestrial planets (Earth, Venus, and Mars) due to differences in interparticle forces. We measured the surface energy (through contact angle measurements) and elastic modulus (through Atomic Force Microscopy) of the Titan aerosol analog (tholin). We find that the surface energy of a tholin thin film is about 70.9 mN/m, and its elastic modulus is about 3.0 GPa (similar to hard polymers like PMMA and polystyrene). For two 20 μm diameter particles, the theoretical cohesion force is therefore 3.3 μN. We directly measured interparticle forces for relevant materials: tholin particles are 0.8 ± 0.6 μN, while the interparticle cohesion between walnut shell particles (a typical model materials for the Titan Wind Tunnel, TWT) is only 0.4 ± 0.1 μN. The interparticle cohesion forces are much larger for tholins and presumably Titan sand particles than materials used in the TWT. This suggests that we should increase the interparticle force in both analog experiments (TWT) and threshold models to correctly translate the results to real Titan conditions. The strong cohesion of tholins may also inform us how the small aerosol particles (∼1 μm) in Titan's atmosphere are transformed into large sand particles (∼200 μm). It may also support the cohesive sand formation mechanism suggested by Rubin and Hesp (2009), where only unidirectional wind is needed to form linear dunes on Titan. Plain Language Summary: On Titan, the sand dunes are made of organic materials that were made in the atmosphere. We made these analog organic sand particles in our lab and measured the cohesion forces between single particles using an atomic force microscope. We find that these organic sand particles are much stickier than analog materials used in the Titan Wind Tunnel. Thus, on Titan, the wind should be stronger in order to blow the organic sand particles than we previously thought. This could also explain how the small organic particles in Titan's atmosphere clumped together to form the much bigger sand particles on Titan's surface. Key Points: Interparticle cohesion between tholin particles is about 0.8 μN, while it is only ∼0.4 μN for walnut shells used in the Titan Wind Tunnel The surface energy of a thin tholin film is about 70.9 mN/m, and its elastic modulus is about 3.5 GPa The strong cohesion between tholin particles suggests that higher threshold wind speed may be needed to form dunes on Titan